Rancang Bangun Sistem Informasi Perpustakaan pada SMK La-Tahzan Berbasis Web - Tarigan, Rehulina; Fuady, Tb Dedy; Korneilis, Korneilis; Harvana, Alvin; Rakhmat, Edy (Jurnal Ilmiah Sains dan Teknologi, 2024)
The library service process at La-Tahzan Vocational School is still manual, such as data collection and recording written on paper media and not yet managed using an application system. This causes the member registration process to be slow, the process of collecting data on books, the process of borrowing and returning books and making reports is carried out by recording in a special book so that obtaining data and information takes a long time. The solution to overcome this problem is to build a website-based library information system. System development uses the System Development Life Cycle method with the waterfall model. Data collection methods were carried out by observation, interviews and literature study. This information system helps library staff in speeding up the member registration process, the book data collection process, the book search process, the process of borrowing and returning books and the process of making reports.